Diagnostic accuracy of renal calculi on ultrasonography taking computed tomography as gold standard - Pathan, Hina; Shazlee, M. Kashif; Iqbal, Junaid; Ali, Ashraf A.; Hameed, Kamran; Ahmed, M. Saad (International Journal Of Community Medicine And Public Health, 2021)
Background: Ultrasonography is a useful modality to diagnose stones and to confirm the occurrence of complications of other renal pathology, so it is important to understand these characteristic findings and other diseases that mimic them. In addition, other imaging modalities such as computed tomography (CT) can be recommended if the clinical or radiological diagnosis is ambiguous. Methods: A group of 325 patients with clinical suspicion of renal calculi were included in this study. Out of these 325 patients 179 (55.0%) were male and 146 (44.9%) were female. All these patients underwent ultrasonography (USG) examination. Final diagnosis was based on CT findings which was done subsequently. Results: The total number of patients comprising the study were 325 who underwent ultrasound examination. After USG and CT scan was done to confirm the diagnosis. Out of 325 patients, 201 patients were confirmed having renal calculi on USG analysis and remaining 103 patients were true negative. Conclusions: The study proves that USG is highly accurate in diagnosing and characterizing renal calculi. USG also guides in defining exact location as well as aids in deciding the medical or surgical approach to be used.